2015
DOI: 10.1080/00222933.2015.1021876
|View full text |Cite
|
Sign up to set email alerts
|

Feeding ecology of the common sun skink,Eutropis multifasciata(Reptilia: Squamata: Scincidae), in the plains of central Vietnam

Abstract: We studied the feeding ecology of Eutropis multifasciata in the tropical plains of central Vietnam to understand better the foraging mode, spatiotemporal and sexual variation in dietary composition, and rarefaction curves of prey-taxon richness for males and females. Stomach contents (n = 161) were collected from October 2013 to May 2014 using a nonlethal stomach-flushing technique. A total of 680 food items (624 animal items and 56 plant items) was found in 161 stomachs of skinks, representing 19 unique anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 59 publications
0
17
0
3
Order By: Relevance
“…Indeed, other studies with polymorphic species have revealed morphometric differences between morphs in body structures, particularly in head anatomy (Huyghe et al, 2007; Bustos-Zagal et al, 2014). Such differences in head size may be linked to variation in bite force, which in turn may be associated with morph differences in diet on the basis of prey size (Gadsden et al, 2011; Ngo et al, 2015) or hardness (Huyghe et al, 2007). We also found no relationship between the total volume of prey and either JL or JW in red males, but significant and negative associations between these variables were observed for yellow males (JL: r s = −0.44, P = 0.05; JW: r s = −0.45, P = 0.04).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, other studies with polymorphic species have revealed morphometric differences between morphs in body structures, particularly in head anatomy (Huyghe et al, 2007; Bustos-Zagal et al, 2014). Such differences in head size may be linked to variation in bite force, which in turn may be associated with morph differences in diet on the basis of prey size (Gadsden et al, 2011; Ngo et al, 2015) or hardness (Huyghe et al, 2007). We also found no relationship between the total volume of prey and either JL or JW in red males, but significant and negative associations between these variables were observed for yellow males (JL: r s = −0.44, P = 0.05; JW: r s = −0.45, P = 0.04).…”
Section: Discussionmentioning
confidence: 99%
“…We used the relative importance index ( I ) to determine the value of each category of consumed prey to each morph. This index includes three parameters for consumed prey (frequency, number, and volume), and is calculated as , where % F is the percentage of occurrence, % N is the numerical percentage, and % V is the volumetric percentage (Biavati, Wiederhecker & Colli, 2004; Ngo et al, 2014). The relative importance index was calculated for each morph overall, and for each morph on a per-season basis (summer, fall, and winter).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These ontogenetic changes in the frequency with which certain food types are consumed may be a consequence of the morphological and physiological restrictions for each age class. For example, it has been reported in some groups of lizards that small individuals consume small, soft prey in comparison to adults (Gadsden et al, 2011;Ngo et al, 2015). However, the nutritional requirements of each age class also could result in changes in diet, since it has been recorded that not all types of prey contribute same amount of nutrients (Leyte-Manrique and Ramírez-Bautista, 2010;Cruz-Elizalde et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Common gliding lizard (Draco volans) feeds mainly on ants, and possibly termites (McGuire and Kiew 2001). Common sun skink (Eutropis multifasciata) specializes on spiders, insect larvae, snails, grasshoppers and crickets (Ngo et al 2015).…”
Section: The Diversity Of Faunal Communitiesmentioning
confidence: 99%